Hyaluronic Acid Correlates With Bone Metastasis and Predicts Poor Prognosis in Small-Cell Lung Cancer Patients - Zhao, Cong; Zhang, Zhiyun; Hu, Xingsheng; Zhang, Lina; Liu, Yanxia; Wang, Ying; Guo, Yi; Zhang, Tongmei; Li, Weiying; Li, Baolan (Frontiers in Endocrinology, 2022)
ABSTRACT Background: Hyaluronan (HA) are one of the essential element of extracellular matrix (ECM), involve in the onset of metastasis in various tumors. The interaction and binding of ligand-receptor HA/ cluster of differentiation-44 (CD44) regulates the physical and the biochemical properties of the ECM, which correlates with an increased propensity toward metastasis and poor survival outcome. Our study aimed to explore HA for predicting metastasis and survival rate in patients with small cell lung cancer (SCLC). Materials and methods: This prospective, cohort study recruited 72 patients with SCLC. Plasma HA and CD44 levels were assayed by enzyme-linked immunosorbent assay (ELISA) for 72 cases before initial systematic treatment (baseline samples) and plasma HA was detected after-2-cycle-chemotherapy (A-2-C-CT) in 48 samples. Logistic regression analysis and Cox proportional risk model were used to determine the independent predictors of distant metastasis and survival rate of patients. Results: Baseline plasma HA was notably associated with bone metastasis [OR (95%CI=1.015(1.006–1.024); p=0.001]. Multivariate logistic regression analysis showed that baseline plasma HA was chosen as an independent predictor of bone metastasis. Either baseline HA or CD44 or both were associated with BM. Dynamic alteration of HA was notably associated with A-2-C-CT clinical efficacy. Multivariate COX regression analysis in forward likelihood ratio way, showed that A-2-C-CT HA was an independent predictor of PFS and OS. Conclusions: HA appears to be used as an independent predictive factor for BM, and dynamic detection of HA can predict prognosis in SCLC patients. The mechanism of HA / CD44 axis in BM of SCLC deserves further exploration.